Social network for tourism «Couchsurfing» as a social phenomenon - A. A. Komarova; O. V. Kryshtanovskaya (Вестник университета)
Any journey is not only a pleasant pastime, but also a way to gain new knowledge. Often a tourist trip requires considerable material costs. Currently, there is a way to save on staying in hotels or hotels throughout the journey. This method has been called Couchsurfing. The relevance of this direction of tourism is particularly increasing in connection with the development of technology and the use of social networks. Couchsurfing promotes cultural exchange and language practice, tolerance and mutual assistance. The article describes a diff ent kind of rationality (social) without receiving monetary payment in an area, where the use of market mechanisms can be beneficial.